SAT0596 Ultrasonographic Evaluation of Subclinicial Enthesitis in Patients Affected by Pediatric Inflammatory Bowel Disease. (9th June 2015) - Batticciotto, A.; Dilillo, D.; Antivalle, M.; Nugnes, M.; Varisco, V.; Ferrari, M.; Santandrea, S.; Mutti, A.; Atzeni, F.; Zuccotti, G.V.; Sarzi-Puttini, P.
Abstract : Background: Joint involvement is the most frequent extra-intestinal manifestation of paediatric inflammatory bowel disease (IBD). Various recent studies focused on the clinical prevalence of enthesitis in children and adults with IBD 1, and others have demonstrated the ability of ultrasound (US) to visualise the acute and chronic signs of entheseal inflammation with greater sensitivity than a clinical examination, although there is a lack of consensus concerning the US definition of entheseal abnormalities and their prognostic value especially in the paediatric field 2 . Objectives: The aim of this study was to evaluate the prevalence of subclinical entheseal involvement in patients with pediatric IBD using a high frequency ultrasound probe. Methods: Twenty-seven pediatric IBD patients (13 with Crohn's disease [CD] and 14 with ulcerative colitis [UC]; 15 females and 12 males; mean age 13.7 years, range 7-21 years) without any clinical signs or symptoms of musculo-skeletal involvement and 24 healthy age- and gender-matched controls (14 females and 13 males; mean age 14.2 years, range 8-20 years) underwent an US examination (ESAOTE MyLAB 70 6-18 MHz linear array transducer). Brachial triceps, femoral quadriceps, Achilles, plantar fascia, and proximal and distal patellar entheses were all scored using the 0-136 Madrid Sonographic Enthesis Index (MASEI). Clinical and clinimetrical variables were assessed in both groups (MASES, BASDAI, BASFI, cHAQ, PCAI/PCDAI). Results: None of the patients had a MASEI score suggesting early spondyloarthritis involvement but their average score was significantly higher than controls (3.15±2.84 vs 0.96±1.12, p=0.0006). There was also a significantly higher percentage of patients with at least one enthesis with power Doppler (PD) score ≥2 (37% vs 16%; p=0.037) and at least one enthesis with dishomogeneous echostructure (59% vs 0%; p=0.000). There were no between-group differences in terms of erosions (0% vs 0%), calcifications (7.4% vs 12.5%; p=0.656) or structural thickness (37% vs 33.3%; p=0.507). In paediatric IBD group we cannot find correlation between the total MASEI score and gender (p=0.12), age (p=0.20), disease duration (p=0.18) or IBD activity (p=0.83). Conclusions: US detectable enthesopathy is frequent in paediatric IBD patients without any clinical signs or symptoms of musculo-skeletal involvement. Further studies involving a larger number of patients are needed to confirm these preliminary data. References: Horton DB. et Al. Enthesitis is an Extraintestinal Manifestation of Pediatric Inflammatory Bowel Disease. Ann Paediatr Rheumatol. 2012; 10:1.0 Bandinelli F, Milla M, Genise S, et al. Ultrasound discloses entheseal involvement in inactive and low active inflammatory bowel disease without clinical signs and symptoms of spondyloarthropaty. Rheumatology (Oxford) 2011; 50:1275-9 Disclosure of Interest: None declared